Applying agent technology in personal and team software process environment: the usability evaluation - Abdullah, Rusli; Misran, Erizal Kamal (Universiti Utara Malaysia, 2010)
Modern system development emphasize on the use of standard and procedures to ensure the system develop meets user needs and of high quality. Standards such as Capability Maturity Model Integration (CMMI), Software Process Improvement and Capability determination (SPICE) and ISO/IEC 90003:2004 are introduced. Personal Software Process (PSP) focusing on improving the individual engineer tasks in software development activities, and can be extended to team development (TSP) of large-scale software systems. To ensure the quality of system, defect must be managed or organized properly. Knowledge Management (KM) provides a solution to manage and promoting shared defect-information as knowledge. Agents technology offer a way to deal with complex systems that have multiple and distinct components, and are often used as a metaphor for autonomous, intelligent entities. Agent technology is also used to enhance a knowledge management system (KMS) based on software agent to increase the performance of knowledge sharing and its utilization. This paper presents an agent-based in a KMS that manages defect-information as knowledge and shares it amongst software engineers who are majoring involved in PSP and TSP system development environment.